Pengaruh Prinsip-Prinsip Good Corporate Governance Pada Kualitas Informasi Keuangan Pdam Kabupaten Buleleng - Devi, Kadek Thasia Windisaptarianti; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2018)
ABSTRACT           In company quality of financial information is important to note, because it  used in economic decision making and to know the condition of the company. Good Corporate Governance need to be implemented in PDAM, because it can reduce agency conflicts between owners and manager. The purpose of this research is to know the influence of the application of GCG on financial information quality of PDAM Buleleng Regency. The respondents are employees of PDAM Kabupaten Buleleng, which are 46 respondents. Determination of sample using nonprobability sampling method with purposive sampling technique.Methods of data collection using questionnaires and using multiple linear regression analysis technique. The result of analysis shows that transparancy, accountability, responsibility, independency and fairness have positive effect on financial information quality of PDAM Buleleng Regency, in this case it is suggested that the government pay more attention to the implementation of GCG especially in BUMD. Keywords : accountability, fairness, independency, responsibility, transparancy